(NsO^INENIQ (B:s (Nw (B6 (NKN(B. /s - (NaLDANOW(B, (NmARK aLEKSANDROWI^s 1886-1957.; (N~ERNY[EW(B, (NaNDREJ aLEKSANDROWI^s ((NmOSKWA (B:s (NpROGRESS(B,s, 1993)
(NmARK aLDANOW(B, (N\MIGRIROWAW[IJ IZ sOWETSKOJ rOSSII WSKORE POSLE oKTQBRQ(B, (NODIN IZ NAIBOLEE QRKIH PISATELEJ RUSSKOGO ZARUBEVXQ(B, (NTWOR^ESTWO KOTOROGO WYSOKO CENIL bUNIN(B, (NkUPRIN(B, (NnABOKOW(B.s
(NkN(B. 3 (544 (NS(B.)s
Keywords: (NrUSSKAQ LITERATURAs -- 2-(NAQ POL(B. 90-(NH GG(B. 19 (NW(B. - 1917 (NG(B.s; (NRUSSKOE ZARUBEVXEs